UPAYA PENCEGAHAN PENULARAN COVID-19 PADA KELOMPOK RENTAN PANGAN DI NAGARI KOTO LAWEH KECAMATAN X KOTO KABUPATEN TANAH DATAR - Melisa Yenti; Arinil Haq; Anggela Pradiva Putri; Indah Tiansy; Diva Febrisia Alfer; Syahrifah Aima (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Covid-19 is a global health problem. On March 11, 2020, WHO declared Covid-19 a pandemic. On May 7, 2020, Indonesia reported 12,776 confirmed cases of Covid-19 and 252 positive cases from West Sumatra Province. Based on scientific evidence, Covid-19 can be transmitted from human to human through coughing/sneezing droplets (droplets). Standard recommendations to prevent the spread of infection are using masks, maintaining distance, washing hands regularly with soap and clean water, and others. The purpose of this activity is to increase public knowledge through billboards that explain information related to Covid-19 that can be seen and accessed by many people, increase food security for vulnerable groups through the distribution of necessities, and distribute non-medical masks as an effort to prevent the transmission of Covid-19. This activity was carried out in Jurong Balai Gadang, Nagari Koto Laweh, X Koto District, Tanah Datar Regency. The implementation of the activity consists of three activities: the first activity, namely the installation of billboards regarding the prevention of transmission of Covid-19 and the new normal COVID-19. The second activity is distributing 40 food packages (containing rice, eggs, cooking oil, sugar) to economically affected people by the Covid-19 pandemic. The third activity is the distribution of masks. The results of the activities obtained are that all activities can be carried out correctly. The public can use the installation of billboards as a source of information that can be accessed easily. The provision of necessities can help food vulnerable communities to meet their nutritional needs during the pandemic. The community can use the distribution of masks to break the chain of transmission of Covid-19. The public should strictly follow the health protocols in their daily life by the information contained on the billboards.